Secondary Structures of Chloroplast trnL Intron in Dipterocarpaceae and its Implication for the Phylogenetic Reconstruction - YULITA, KUSUMADEWI SRI (HAYATI Journal of Biosciences, 2013)
Unambiguous insertion-deletion events were previously identified in trnL intron of 110 species of subfamily Dipterocarpoideae (Dipterocarpaceae).  These indels are associated with the formation of four stem loop structures and featuring characteristic for generic/infra-generic level depended upon which taxonomic classifications are followed. Phylogenetic analyses were performed by including and excluding these structures to examine the robustness of resulted topologies. Results indicated that inclusion of such structures yielded more resoved topologies, and that none of the stemloop structures were homoplasious. Results of this present study was also in agreement with the previous molecular phylogenetic studies that using several genes of cp genomes in that tribe Dipterocarpae was polyphyletic by the placement of all members of the genus Dipterocarpus within tribe Shoreae, and that tribe Shoreae was a potential monophyletic group. The phylogenetic relationships between  variable genera of Hopea and Shorea was also in accordance to earlier studies that suggested a potential monophyly of the two with inclusion of Parashorea and Neobalanocapus heimii. Genera that were recived strong branch support (Dipterocarpus, Dryobalanops, Vatica, and Stemonoporus) possessed certains indels exclusive to each and this may contributed to the monophyletic nature of these genera.